Innovation and expansion: Product innovationand expansion in insurance in South Africa. The case of Sanlam, 1920–1998 (Historia, 2021)
The insurance industry is generally perceived to be a conservative, risk averseCenterprise following market developments rather than leading them. This article explores the development of innovation in the South African long-term insurance market in the context of the development of the South African economy after the formation of the Union of South Africa. A leading role player in this market is Sanlam, a company leading the South African long-term insurance industry in product innovation. This article investigates the strategy used by Sanlam to establish itself in a market dominated by British insurance companies. It then  explores the use of product innovation by Sanlam since the early 1920s to expand its market share. The competitive advantage acquired by Sanlam in the insurance industry by the end of the twentieth century paved the way for subsequent expansion and diversification.   Afrikaansŉ Algemene aanname oor die versekeringsbedryf is dat dit ŉ konserwatiewe, risikovermydende sektor is wat eerder markneigings navolg as om dit te inisieer. Hierdie artikel ondersoek die ontwikkeling van innovering in die Suid-Afrikaanse langtermynversekeringsmark teen die agtergrond van die ontwikkeling van die ekonomie na die totstandkoming van die Unie van Suid-Afrika. ŉ Onderneming wat ŉ leidende rol in hierdie mark in Suid-Afrika gespeel het, is Sanlam wat in die langtermynversekeringsmark op die voorpunt van produkontwikkeling is. Verder word ondersoek ingestel na die strategieë wat deur Sanlam gevolg is om die maatskappy te vestig in hierdie mark wat aanvanklik deur Britse maatskappye oorheers is. Die artikel ondersoek Sanlam se gebruik van produk-innovasie sedert die vroeë 1920’s om hul markaandeel te vergroot. Die mededingende voordeel wat Sanlam teen die einde van die twintigste eeu verwerf het, het die grondslag gelê vir daaropvolgende uitbreiding en diversifikasie.
Keywords: Product development; longevity; long term insurance; disability; premiums; investments; Produkontwikkeling; langlewendheid; langtermynversekering; ongeskiktheid; premies; beleggings